Ethnoichthyology of Fishing Communities in the Lower Valley of Ouémé in Benin, West Africa - Djidohokpin, Gildas; Sossoukpè, Edmond; Adandé, Richard; Voudounnou , Juste V.; Fiogbé, Emile D.; Haour, Anne (Ethnobiology Letters, 2020)
Ethno-ichthyological knowledge can improve fisheries management. This study covers interactions between ecological, morphological, and sociocultural aspects pertaining to the fish of the Tovè River, which is located in the largest fishing area in the Republic of Benin (Ouémé Valley), West Africa. In particular, data were collected on fishing methods and techniques, fishing equipment, and ichthyofauna by noting vernacular names followed by identification traits, taste and dietary value, medicinal use, and related knowledge of different species. Through data related to names given locally to fish, this paper highlights the manner in which physical or behavioral traits are coded in terminology. Most of these species have a high market value, either because they are considered to be delicacies and/or for their medicinal uses. The results suggest that ethno-ichthyological information can successfully be applied to improve fish conservation and fisheries management.